Critical Factors for ICT Adoption in Industrial Sector Micro and Small Enterprises (MSEs) - Vasquez Reyes, Edgar Fernando (2022)
Micro and small-sized enterprises (MSEs) employ approximately 60% of the economically active population (EAP) in our country, but only 15% of them have access to information and communication technologies (ICTs). Therefore, it is believed that these companies do not understand ICTs, do not value them or give them due importance and are reluctant to adopt and use ICTs. This non-experimental research aims to find evidence of the relationship between critical factors and the adoption of information technologies in this type of company. To this end, a survey was conducted among 179 businessmen in Metropolitan Lima. Following the evaluation and analysis of the data obtained, it was found that 11 factors have a positive correlation for the adoption of information technologies and 3 are rejected because the significance level obtained is greater than 0.05. Thus, a new model of ICT adoption based on the 11 accepted factors is created for this type of company.